PROFIL PRESEPAN OBAT PADA PASIEN PEMBESARAN PROSTAT JINAK ATAU BPH (BENIGN PROSTATIC HYPERPLASIA) TAMSULOSIN DAN DUTASTERIDE DI INSTALASI RAWAT JALAN RUMAH SAKIT “X” CIPUTAT PERIODE OKTOBER-DESEMBER 2024 - Dewantoro, Agung; Dewi, Bheta Sari; Rahajeng, Suny Koswara (PHRASE (Pharmaceutical Science) Journal, 2025)
Benign prostatic hyperplasia (BPH) is a term used in histopathology to describe the presence of enlarged stromal and epithelial cells in the prostate gland.  In essence, BPH mostly affects elderly men whose testes are still capable of making testosterone. According to earlier research, using dutasteride and tamsulosin together may have greater therapeutic results for BPH and significantly lower the chance that symptoms may worsen. Purpose:  The objective of this study was to identify salient features of Tamsulosin and Dutasteride prescriptions for benign prostatic enlargement (BPH) at Ciputat "X" Hospital's outpatient clinic from October to December 2024.. Methods: This research method is descriptive, the data is taken restropectively, namely research that looks back, meaning data collection from medical records of outpatients with BPH diagnoses. Results: This study showed that, 101 samples of BPH patients were obtained, the most BPH patients occurred at the age of 56-65 (47.5%), the most work status was self-employed (44.6%), the mosttypes oftherapy were combination therapy oftamsulosin with dutasteride (56.4%), α1-blocker drug classes that got a percentage (100%), the most length of therapy was 1 month (98.0%), and other groups of drugs prescribed Antibiotics (37.5%).